PERENCANAAN DAN STRATEGI KOMUNIKASI YANG TEPAT MERUPAKAN SOLUSI KOMUNIKASI YANG EFEKTIF - Melita, Yerah (Jurnal Insani, 2019)
In everyday life communication is very important and needed by every human being, because without communication humans will "die". In practice the communication is not always in accordance with expectations, sometimes it becomes tasteless, not on target, not connected, the realization of the communicator's communication motives often even failure in communication or in other words the communication is not effective. By realizing that communication by humans is not always smooth and successful in accordance with the expectations of both parties, both those who give and those who receive, then it takes a careful planning and also the right strategy for communication.